HUBUNGAN CITRA HOTEL DAN KEPERCAYAAN PELANGGAN: SURVEI PELANGGAN HOTEL MELATI DI SULAWESI TENGAH - Rombe, Elimawaty (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2011)
This research designed as quantitative method using explanatorysurvey while verification is the main objective. The aim of this study is to examine the relationship of customer image and trust of Hotel Melati III and IV in Middle Sulawesi. Hypothesis testing was conducted through data collection directly from the field. Thus, this research can be classified as field study. The results showed that image and trust has a strong positive correlation. The positive sign indicated that the increase in image would be followed by increase in trust and vice versa.